Comparing triggers to visual disturbances among individuals with positive vs negative experiences of hallucinogen‐persisting perception disorder (HPPD) following LSD use. (27th June 2017) - Lev‐Ran, Shaul; Feingold, Daniel; Goodman, Craig; Lerner, Arturo G.
Abstract : Background and Ojective: Exploring differences in visual disturbances and triggers between Hallucinogen‐Persisting‐Perceptual‐Disorder (HPPD) Type I ("positive/benign") and II ("negative/distressing"). Methods: Forty individuals with HPPD and prior LSD use completed clinical questionnaires. Results: The most common type of visual disturbances among individuals with HPPD I and II was slow movement of still objects and trailing phenomena, respectively. Those with HPPD I were more likely to report experiencing disturbances in dark environment, while looking at a still or moving object and during sexual intercourse. Discussion And Conclusions: HPPD I and II differ in terms of visual disturbances and triggers, possibly representing different phenomena existing on the same spectrum. Scientific Significance: Our study indicating differences in triggers to HPPD I and II adds to existing literature on differences in visual disturbances between the two subtypes. Further research elucidating additional differences between the subtypes of HPPD is needed. (Am J Addict 2017;26:568–571)